Anthocyanin and polyphenol contents of Antidesma thwaitesianum Müll. Arg. berry juice being stabilized by protein matrices - Rosruen, T.; Vadhanasindhu, V.; Phuwapraisirisan, P. (International Journal of Agricultural Technology, 2021)
The berry juice of Antidesma thwaitesianum Müll. Arg. has been recognized as a rich source of anthocyanin, proanthocyanidin and polyphenol. However, the rapid decrease in polyphenol contents, antioxidant activity and sensory perception during storage hamper its development as health-promoting products. To circumvent this problem, we introduced a method called anthocyanin-protein sorption (APS) to retard polyphenols depletion. The AT berry juice was adsorbed on five different proteins (soy protein isolate (SPI), whey protein isolates (WPI), soybean powder (SBP), black bean powder (BBP), and red bean powders (RBP)), and the matrices obtained after the sorption were evaluated for anthocyanin, proanthocyanidin and total phenolic content along with the antioxidant activity. After four-week storage, all of polyphenol content and the antioxidant activity of AT berry juice decreased dramatically whereas those of anthocyanin-protein matrices were slightly declined (5-21%) over twenty-four-week observation. As protein investigation soy protein isolate (SPI) was most effectively stabilized AT berry juice polyphenols with 5-8% decrease in anthocyanin, proanthocyanidin and total phenoliccontents